Evaluation of in vitro Anti-Inflammatory Activity of Zolpidem - Lalit, Rhea Surana; Karthika, K; Ramasamy, Kavitha (International Journal of Pharmaceutical Investigation, 2025)
Objectives Zolpidem, a novel non-benzodiazepine sedative, has shown antioxidant, muscle relaxant, anti-convulsant and anti-anxiety properties. The Objective of our study is to evaluate it’s in vitro anti-inflammatory activity. Materials and Methods Three assays were done: Protein Denaturation, Erythrocyte Membrane Stabilization and Proteinase Inhibition Assays using standard techniques. Results Zolpidem showed maximal inhibition of 88.34 ± 0.09%, 82.41 ± 0.41% and 79.20 ± 0.41% in the Protein Denaturation, Erythrocyte Membrane Stabilization and Proteinase Inhibition Assays. Conclusion This shows that Zolpidem possesses excellent anti-inflammatory activity and untapped potential to be used in neurodegenerative diseases. Further in vivo studies could be done to further explore this activity.
Keywords: Erythrocyte Membrane Stabilization and Proteinase Inhibition; Protein Denaturation; Zolpidem